2006
DOI: 10.4012/dmj.25.241
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Methacrylate Monomers in Human Saliva

Abstract: INTRODUCTIONDegradation of dental resins in human saliva, that lead to decrease in mechanical strength and surface hardness, have been reported in in vitro studies 1,2) . The results of these studies suggested that such degradation arose from the chemical degradation of methacrylate polymers due to enzyme-catalyzed hydrolysis reaction of ester bond. However, methods that can adequately investigate the enzymatic degradation mechanism involved in the breakdown of methacrylate polymers are not available. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
0
25
0
1
Order By: Relevance
“…Different strategies have been developed to enhance the hydrolytic stability of dentin adhesive resins. These strategies include changing the monomer structure with an emphasis on increasing the hydrophobicity of the monomers by introducing urethane groups [1719], branched methacrylate linkages [20], or ethoxylated BisGMA (BisEMA) [21]. The extent and rate of water uptake are depressed temporarily, but most of the materials still reach saturation within 7–60 day [22].…”
Section: Introductionmentioning
confidence: 99%
“…Different strategies have been developed to enhance the hydrolytic stability of dentin adhesive resins. These strategies include changing the monomer structure with an emphasis on increasing the hydrophobicity of the monomers by introducing urethane groups [1719], branched methacrylate linkages [20], or ethoxylated BisGMA (BisEMA) [21]. The extent and rate of water uptake are depressed temporarily, but most of the materials still reach saturation within 7–60 day [22].…”
Section: Introductionmentioning
confidence: 99%
“…UDMA, another commonly used monomer that contains urethane bonds, has greater stability against hydrolysis when compared to BisGMA. In human saliva, BisGMA undergoes complete hydrolysis by 48 h while after 72 h of incubation more than 70% of UDMA is still left in solution [28]. Work by Hagio et al [28] has shown that modifying BisGMA by replacing the hydroxyl moieties with short hydrocarbon side chains coupled via a urethane bond increases the hydrolytic stability in the presence of human saliva [28].…”
Section: Discussionmentioning
confidence: 99%
“…In human saliva, BisGMA undergoes complete hydrolysis by 48 h while after 72 h of incubation more than 70% of UDMA is still left in solution [28]. Work by Hagio et al [28] has shown that modifying BisGMA by replacing the hydroxyl moieties with short hydrocarbon side chains coupled via a urethane bond increases the hydrolytic stability in the presence of human saliva [28]. The enhanced stability was attributed to the difference in molecular structure, such as steric hindrance and the addition of the urethane bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of acrylate dental materials to degradation by esterases is well established [119,[122][123][124][125][126]. The esterase-catalyzed degradation of monomethacrylates, dimethacrylates and commercial dental resins has been documented in solution [122][123][124]126], in saliva samples [124,125,127], and in vivo [92]. In vitro studies have typically used one or more of the following esterases: cholesterol esterase (CE; EC 3.1.1.13) [122,124,126] acetylcholinesterase (ACHE; EC 3.1.1.7) [122,126] and pseudocholinesterase (PCE, aka butyrylcholinesterase; EC 3.1.1.8) [122,124,126].…”
Section: Iva Degradation Of the Hybrid Layermentioning
confidence: 98%